(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
During the last few years combined production of electricity and heat based on biomass gasification technology and on gas utilization in gas-fired engines has been widely reconsidered. This method is more sustainable and environmentally friendly provision of energy in the future. Latvia is rich in forests and the wood processing industry is developing very fast, giving about 4.5 mill. m3 of woods residue per year. The use of wood residue does not follow the increase of wood production. In Latvia we have abundant biomass resources such as wood harvesting and wood processing residues, waste wood and sawdust. As a first attempt to introduce biomass gasification technology in Latvia some researchers at the faculty of engineering of LUA are developing an integral small scale combined heat and power (CHP) system based on a used Russian-made diesel-alternator set with electrical output 100 kWe. The diesel is converted to dual fuel gas engine, using producer gas as the main fuel and gas oil as pilot fuel. To get sufficiently clean (tar content ? 250 mg/m3) woodgas for using in IC engine a downdraft type of gasifier was chosen designed and constructed on the “IMBERT” gasifier principles. The test runs of the first experimental model showed that the engine does not develop expected power because of high resistance of gasifier and gas cleaning system does not work sufficiently enough. There was rather high level of tar content in woodgas because the temperature in the reduction zone was to low. Calculations were carried out and a new technological scheme of gasification system was worked out, introducing innovative ideas aimed on improving the working parameters. The experiments and calculations showed that such a type of CHP plant could be a technologically and economically interesting option for small sawmills and farms in rural areas.